Psychological distress, job satisfaction and work engagement: a cross-sectional mediation study with a sample of Palestinian teachers. Issue 3 (4th May 2021) - Pepe, Alessandro; Addimando, Loredana; Dagdukee, Jamal; Veronese, Guido
ABSTRACT: The aim of the present study was to evaluate the relationship between psychological distress and job satisfaction in a sample of Palestinian in-service primary and lower secondary teachers (N = 380). Specifically, we cross-sectionally tested the hypothesis that the association between teachers' job satisfaction and psychological distress would be fully mediated by their levels of work engagement. Participants completed the Arabic versions of the Teacher Job Satisfaction Scale (TJSS-9), General Health Questionnaire (GHQ-12) and Utrecht Work Engagement Short-form scale (UWE-SF). As is conventional in mediation studies, the data were analysed using structural equation modelling and decomposition of direct and indirect effects. The moderate positive relationship identified between job satisfaction and psychological distress was fully mediated by work engagement (F = 17.05, p < .001, R 2 = .16). This finding suggests that in order to reduce the effect of low job satisfaction on teachers' psychological distress, organisational policies and practices should include a focus on enhancing their level of engagement.